Circulating Endothelial Cells as a Marker of Endothelial Injury in Severe COVID -19. (19th August 2020) - Guervilly, Christophe; Burtey, Stephane; Sabatier, Florence; Cauchois, Raphaël; Lano, Guillaume; Abdili, Evelyne; Daviet, Florence; Arnaud, Laurent; Brunet, Philippe; Hraiech, Sami; Jourde-Chiche, Noémie; Koubi, Marie; et al.
Abstract: Beside the commonly described pulmonary expression of the coronavirus disease 2019 (COVID-19), major vascular events have been reported. The objective of this study was to investigate whether increased levels of circulating endothelial cells (CECs) might be associated with severe forms of COVID-19. Ninety-nine patients with COVID-19 were enrolled in this retrospective study. Patients in the intensive care units (ICU) had significantly higher CEC counts than non-ICU patients and the extent of endothelial injury was correlated with putative markers of disease severity and inflammatory cytokines. Together, these data provide in vivo evidence that endothelial injury is a key feature of COVID-19.